Hubungan Kebugaran Jasmani Terhadap Tingkat Konsentrasi Siswa di SMAN 9 Bekasi - Aprillia Krissanthy; Febi Kurniawan; Citra Resita (Universitas Singaperbangsa, 2020)
This study aimed to determine whether there is a correlation between physical fitness and student concentration levels in physical education has. This research uses a quantitative approach with a survey method. The subject or research population used is class X of SMA Negeri 9 Bekasi City, amounting to 355 people. The research sample consisted of 23 students with a simple random sampling technique. The instrument used in this study was the level of physical fitness of students measured using the Indonesian Physical Fitness Test (TKJI) consisting of several test series, such as a: a) running 60 meters, b) pull -up60 seconds, c) 60 seconds of sit-ups, d) jumping upright, and e) running 1200 meters. Then the concentration of student learning is measured using the Grid Concentration Exercises test instrument. Retrieval of data in this study through the provision of tests and measurements through surveys. The results showed rhitung = 0.578 ≥ rtabel = 0.433, which means that that there was a significant relationship between the level of physical fitness and the concentration level of class X students of SMA Negeri 9 Bekasi City. The result of the determinant coefficient (r2) is 33.4% and the rest of the calculation result is 66.6%, the concentration level is determined by other factors.